The possibility of physiotherapy treatment after injury of anterior cruciate ligament - Korabiusz, Katarzyna; Fabian- Danielewska, Anna; Wawryków, Agata (Journal of Education, Health and Sport, 2017)
Introduction: Damage of ACL represents approximately 50% of all internal damages of knee joint after its injury. According to statistics, 1 person out of 1000 residents suffers from ACL injury. Approximately 3 thousand reconstructions of ACL are performed yearly therefore it is very important to work out an optimal post-operative rehabilitation. Through this, it is possible to reduce pain indispositions and restore a good joint stabilization and improved quality of life. Goal of dissertation: Goal of this dissertation is a review of literature about available physiotherapy methods used after injury of anterior cruciate ligament. Conclusion: There are many physiotherapy methods used after injury of ACL. Methods proposed in literature increase range of movement in knee joint, reduce pain and restore a good joint stabilization The most often used methods are: transdermal nerves stimulation TENS, criotherapy, magnetic field, ultrasounds, LASER, electrostimulation, interferention, kinesitherapy and kinesiotaping, Rehabilitation significantly reduces pain indispositions and has a positive influence on quality of life of patients after ACL injuring.